Efforts to Improve the Public Service Quality: Implementation of a Modern Electronic Tax System, Self-Efficacy, and Taxpayer Compliance - Purnamasari, Dyah; Tahir, Rusdin (Universitas Padjadjaran, 2025)
The success of tax revenue depends on the effectiveness of tax administration that improves taxpayer compliance, the quality of public services, and the uniform implementation of tax provisions. This study aims to explore the factors that affect the quality of public services with a focus on taxpayer compliance, including the influence of e-registration, e-filing, e-efficacy, and digital literacy. A quantitative approach was used with a survey of 535 respondents (416 individual taxpayers and 119 fiscal authorities) at the Directorate General of Taxes of West Java I, II, and III. Statistical analysis was carried out using SEM with the Lisrel application. The results of the study show that e-registration has a positive and significant effect on taxpayer compliance, while e-filing affects compliance but is not significant. Self-efficacy has a positive and significant effect on taxpayer compliance, while digital literacy has an effect but is not significant. At the same time, e-registration, self-efficacy, e-filing, digital literacy, and taxpayer compliance have a positive and significant effect on the quality of public services. These findings make a theoretical contribution by clarifying the factors affecting taxpayer compliance and practical implications for improving tax administration strategies that can improve taxpayer engagement and compliance.